Chlorhexidine (2.5%)–alcohol versus povidone-iodine (10%) alcohol for surgical site antisepsis in cesarean section in a tertiary care hospital – A prospective observational and analytical study - Dasgupta, Shyamal; Das, Pallabi; Pan, Avijit; Ghosh, Chiranjit; Roy, Poulami; Mukherjee, Srijita; Barua, Medha; Patel, Hetal; Biswas, Avijit (Asian Journal of Medical Sciences, 2022)
Background: Rising trends of cesarean section globally demand identification of most suitable pre-operative antiseptic agent to minimize surgical site infections (SSI) and its consequences. Aims and Objectives: The aims of this study were to determine, compare, and analyze SSI developing following the use of chlorhexidine (2.5%)–alcohol and povidone-iodine (10%) alcohol as pre-operative antiseptic agents in cesarean section. Materials and Methods: A prospective, observational, and analytical study was conducted in a tertiary care center for 1 year, where 300 women receiving pre-cesarean surgical site antisepsis with chlorhexidine (2.5%)–alcohol were compared with another 300 receiving povidone-iodine (10%) alcohol. Results: The two study groups were compared in terms of various sociodemographic and clinical parameters which might act as confounding factors and were found to be similar. As compared to women receiving povidone-iodine (10%) alcohol, women receiving chlorhexidine (2.5%)–alcohol had significantly lesser incidence of overall (P<0.001), superficial (P<0.001), and deep (P<0.05) SSI, infections developing at 48 h–5 days (P<0.001) and at 5 days–30 days (P<0.05). There was no significant difference among the two groups with respect to wound swab culture reports and post-SSI inflammatory markers. As compared to the povidone-iodine group, in the chlorhexidine group, a significantly (P<0.05) greater percentage healed with meager dressing and a significantly (P<0.05) lesser percentage required secondary suturing and readmissions and had a significantly (P<0.05) lesser mean duration of hospital stay. Conclusion: Chlorhexidine (2.5%)–alcohol appears to be a better pre-operative surgical site anti-septic agent than povidone-iodine (10%) alcohol in cesarean section.